2003
DOI: 10.1016/s0012-1606(02)00048-9
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of sonic hedgehog signaling alters growth and patterning of lingual taste papillae

Abstract: Taste buds on the anterior part of the tongue develop in conjunction with epithelial-mesenchymal specializations in the form of gustatory (taste) papillae. Sonic hedgehog (Shh) and Bone Morphogenetic Protein 4 (BMP4) are expressed in developing taste papillae, but the roles of these signaling molecules in specification of taste bud progenitors and in papillary morphogenesis are unclear. We show here that BMP4 is not expressed in the early tongue, but is precisely coexpressed with Shh in papillary placodes, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
162
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(172 citation statements)
references
References 61 publications
7
162
0
Order By: Relevance
“…This reporter allele comprises a lacZ knockin to the BMP4 coding region and regulation of transcription of this locus should thus be unaltered. Further, ß-galactosidase expression in this mouse line has been shown repeatedly and in a variety of tissues and developmental stages to accurately reflect BMP4 mRNA expression [44,45,48], including faithfully replicating BMP4 mRNA expression in the developing taste bud progenitor cells of mouse embryos [41,60]. Nonetheless, we were unable to confirm this concordance in adult mouse taste epithelium.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This reporter allele comprises a lacZ knockin to the BMP4 coding region and regulation of transcription of this locus should thus be unaltered. Further, ß-galactosidase expression in this mouse line has been shown repeatedly and in a variety of tissues and developmental stages to accurately reflect BMP4 mRNA expression [44,45,48], including faithfully replicating BMP4 mRNA expression in the developing taste bud progenitor cells of mouse embryos [41,60]. Nonetheless, we were unable to confirm this concordance in adult mouse taste epithelium.…”
Section: Discussionmentioning
confidence: 75%
“…BMP4 regulates embryonic development of taste papillae [41,42], but its expression and role in adult taste buds has not been investigated. We show here that BMP4, via a genetically engineered LacZ reporter mouse line, is expressed in a subset of cells associated with mature taste buds, but that the pattern of expression differs between the circumvallate and fungiform taste papillae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports with rodent tongue cultures showed that neutralizing Shh with a monoclonal anti- body (5E1) or blocking Shh's activity with cylcopamine enhanced taste papillae formation (both size and number) accompanied by increased expression of Shh (15,16,18). Because we have seen coexpression of Wnt signaling elements and Shh, and because we determined that Wnt/␤-catenin signaling upregulates Shh expression, we set out to more closely examine interactions of these two signaling pathways.…”
Section: Inhibition Of Shh Signaling Increases Wnt/␤-catenin Signalinmentioning
confidence: 99%
“…Expression of Shh, Bmp, Noggin, Fgf, and EGF is associated with taste papilla initiation and patterning, indicating the potential role of these factors in taste papilla development (11)(12)(13)(14). Disruption of Shh signaling during the prenatal period by neutralizing antibody or by cyclopamine caused aberrant development and patterns of fungiform papillae (15,16). Although Wnt signaling pathways are critical in the development of many epithelial tissues, they had not been examined in the developing taste system, nor had their interaction with Shh been previously examined in the developing taste papillae.…”
mentioning
confidence: 99%